The Influence of Placement, Workload, and Communication Skills on Employee Performance at BPJS Ketenagakerjaan in Makassar City - Inrayani Inrayani; Andi Jam’an; Samsul Rizal (Eduvest - Journal of Universal Studies, 2024)
This study aims to determine and analyze the Influence of Placement, Workload and Communication Skills on Employee Performance of BPJS Ketenagakerjaan Makassar City. This type of research is quantitative research with a sample of 77 respondents using a questionnaire as a source of data collection, the analysis used is Multiple Linear Regression Analysis using the SPSS V.24 application. The results of the study indicate that: 1. Placement has a positive and significant effect on employee performance 2. Workload has a negative but not significant effect on employee performance and 3. Communication skills have a positive and significant effect on employee performance.